Implementasi Pelimpahan Kewenangan Bupati Kepada Camat dalam Rangka Otonomi Daerah (Studi di Kecamatan Kambera dan Kecamatan Kota Waingapu Kabupaten Sumba Timur) - Hukapati, Umbu Yabbu; Yohanes, Saryono; Monteiro, Josef Mario (Law Faculty, Nusa Cendana University, 2024)
This study aims to analyze the implementation of Regent's authority delegating to Subdistrict Head in the context of regional autonomy and the impediment factors of the implementation of the Subdistrict Head authority at Kambera and Kota Waingapu Subdistrict of East Sumba Regency. This was an empirical judicial research with qualitative and conceptual approach. The data processing technique used were editing, clarification, tabulating, and verification, and analyzed by qualitative descriptive accord with the law theories, principles and norms. The results revealed that the Head of Kambera and Kota Waingapu Subdistrict have implemented the authority delegated by the Regent of East Sumba eventhough not optimal yet, which were (1) licensing services of commercial sector of issuing Micro and Small Enterprises (MSEs/UMK) Business License, by publishing code of conduct terms in running the MSEs business while the issuing and signing up the license by OSS RBA (Online Single Submission Risk-Based Approach) at the Capital Investment and Integrated One-Stop Services Agency (CIIO-SSA) of East Sumba Regency Government, (2) non licensing services of village and society/community empowerment sector by budget allocation for family welfare empowerment (PKK) activities and the homelesses; listing the village inhabitants deserved for and distribution the social aids; developing the young millenial generations through engagement in farming, breeding, running a business, and trading; (3) evaluation of the program by capacity developing of the Chiefs and all human resources apparatus set of the villages in drafting the Village General Revenue and Expenditure Budget (APBDes); accompanying in the planning, establishing, and implementing the APBDes, APBDes draft and village budget evaluation, and APBDes concerned village regulations evaluation quarterly and every year. The impediment factors of the implementation of the Subdistrict Head authority were (1) the minimity of MSEs Business Licensing socialization, (2) the utilities and infrastructures lacking which were the availability of services hall, office appliances such as computer, printer, operational motor vehicle, and budget, (3) the lack of coordination between the subdistrict with the villages government, neighborhood asociation (RT/RW) of the MSEs Business licensing services, listing the MSEs businessmen, acceptor listing and distribution of the social empowerment aids, and had not ever coordinated with the regency government and the CIIO-SSA, and (4) the poor quality of the subdistrict government human resources. Researcher suggests that the concerned stake holders which are the chief and the all human resources apparatus set of the subdistricts and regency governments, and CIIO-SSA should more enhancing the synergy in solution finding efforts of the impediment factors of the implementation of the Regent’s authority delegating to the Subdistrict Head such as by routine and continuously coordination in order to maintain and enhancing the services performance and regional welfare development